Net effective carbon rates - Garsous, Grégoire (OECD Taxation Working Papers, 2023)
Building on an approach pioneered in the OECD's Taxing Energy Use for Sustainable Development report, this paper develops a methodology to estimate effective carbon rates net of pre-tax fossil fuel support: the Net Effective Carbon Rates (Net ECR). This exercise is made possible by combining the two OECD databases: the Taxing Energy Use and Effective Carbon Rates database (the backbone of the newly established OECD series on Carbon Pricing and Energy Taxation) and the Inventory of Support Measures for Fossil Fuels. The paper then explores potential use cases of this new indicator. In particular, it explains how the Net ECR can be used to calculate fossil fuel support (FFS) against external carbon pricing benchmarks and why such an approach facilitates comparisons of FFS across countries and over time. The paper's conclusions include avenues for future research